The Conservation challenges of Burkitu Community forest, Gasera District, Bale Robe, Ethiopia: Conservation challenges of Burkitu Community forest. - Abdela, Ahmed (Sustainability Science and Resources, 2024)
Aims:The study focused on the difficulties facing the Burkitu community forest in Southeast Ethiopia's Gasera District Bale Zone in terms of conservation. The Burkitu Community Forest got its name because the land is owned by a legally recognized group of individuals known as Burkitu. The woodland is 18.62 hectares in size and borders Ganda-Wotechimo and Gasera 01 on both sides. Materials & Methods: Questionnaires, interviews, and focus group discussions were used to gather data. SPSS statistical software was used to evaluate the observed and collected data and produced frequency and percentage charts. Findings:Burkitu Community Forest faces numerous conservation issues, such as poor governance, deforestation, unclear boundaries, low local community awareness, and strained relationships between community forest members and local officials. Conclusion:Financial assistance, raising local community awareness, drawing clear boundaries, maintaining unity between community forest members and the leader, and limiting the leader's lack of commitment are all crucial control measures to protect Burkitu community forest.